MENINGKATKAN PERTUMBUHAN EKONOMI HIJAU MELALUI TINGKAT PENDAPATAN DAN PENDIDIKAN - Huda, Nurul; Imron, Moch; Sarimaryoni, Hamdi (Bisman (Bisnis dan Manajemen): The Journal of Business and Management, 2024)
Green economic growth can have a negative impact on poor communities. The green economic transition can cause an increase in energy prices which can have a negative impact on poor communities. The green economic transition can cause job losses, especially for sectors whose supporting materials depend on intensive natural resources. This research aims to analyze the influence of poor people's income with the independent variables being the level of income and education on the affected green economists. This research uses primary data and secondary data. The research results show that people's income has a negative influence on the impact of the green economy. An increase in people's income can reduce the negative impact of the green economy. Education has a positive effect on increasing the growth and sustainability of the green economist program in the Jepara region.